2009
DOI: 10.1099/mic.0.029884-0
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of the ilvB1 gene in Mycobacterium tuberculosis leads to branched-chain amino acid auxotrophy and attenuation of virulence in mice

Abstract: Acetohydroxyacid synthase (AHAS) is the first enzyme in the branched-chain amino acid biosynthesis pathway in bacteria. Bioinformatics analysis revealed that the Mycobacterium tuberculosis genome contains four genes (ilvB1, ilvB2, ilvG and ilvX) coding for the large catalytic subunit of AHAS, whereas only one gene (ilvN or ilvH) coding for the smaller regulatory subunit of this enzyme was found. In order to understand the physiological role of AHAS in survival of the organism in vitro and in vivo, we inactivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
55
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 36 publications
5
55
0
Order By: Relevance
“…This confirmed that the selected clones were mc 2 ⌬ilvH mutants. The inactivation of the large subunit of acetohydroxyacid synthase, ilvB1 has been shown to be auxotrophic (54). Our results suggest that the small subunit of acetohydroxyacid synthase ilvH is also essential in the absence of BCAA complementation.…”
Section: Resultssupporting
confidence: 48%
See 1 more Smart Citation
“…This confirmed that the selected clones were mc 2 ⌬ilvH mutants. The inactivation of the large subunit of acetohydroxyacid synthase, ilvB1 has been shown to be auxotrophic (54). Our results suggest that the small subunit of acetohydroxyacid synthase ilvH is also essential in the absence of BCAA complementation.…”
Section: Resultssupporting
confidence: 48%
“…4B). AHAS is composed of the IlvB (large) and IlvH (small) subunits encoded by the ilvB and ilvH genes, respectively (54,55). The genomic organization of ilvH and its flanking regions is illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is extremely urgent to develop novel, less-toxic and effective fungicides for the management of FHB. Enzymes involved in certain amino acids biosynthesis (e.g., BCAAs) have been regarded as attractive fungicide targets due to their absence in mammals and the important biological functions of the genes encoding for these enzymes in yeasts and filamentous fungi [1321]. …”
Section: Introductionmentioning
confidence: 99%
“…Also, knockout strains of acetohydroxyacid synthase ( ilvB1 ) were attenuated for growth and virulence in mice15. L-threonine acts as a precursor for L-isoleucine and flux from threonine to isoleucine is under allosteric control of threonine dehydratase and acetohydroxy acid synthase (AHAS).…”
mentioning
confidence: 99%